Avaliação da eficácia dos trabalhos de Auditoria Independente no Brasil, por profissionais de empresas de capital aberto - Rezera, Evandro Luis (2007)
Trust is the main product it is expected from the auditor s work, because it provides credibility to its report and, consequently, to the audited financial statements. In addition to high ethical standards and technical expertise inherent to its reviewer role, the external auditor, in order to generate the expected trust, depends on the perception society has in relation to auditor s ethical and technical attributes. Aiming to obtain the perception from the professionals that work fo private companies and that are directly involved with the external auditor s work, it was reviewed the bibliography considered relevant on auditing and concerning subjects, in Brazil and abroad, especially ethics, fraud, independence and factors that potentially affet the auditing quality. 28 companies participated in this analysis, through the perceptions obtained from 28 executives that work for such companies. The data was collected through a questionnaire applied between April and May 2007. The main results of this analysis comprise the classification of the external auditors as the less responsible agent for identify relevant fraud in an audited entity, compared to other four agents, and the attribute of the grade 4 to the auditor, in a scale ranging from 1 to 5, in relation to its efficacy to identify relevant frauds and errors that affet the financial statements. The main conclusions of this work are that the auditing clients do not exaggerate the responsibility of the auditor to detect relevant frauds and errors to the financial statements, and believe the auditors are efficient to identify such frauds and errors. In addition, this work identified certain areas of concern to the auditor, that may support a thorough understanding of the current situation of the profession and its future challenges